Analisis Faktor Yang Mempengaruhi Penyerapan Tenaga Kerja Dan Efisiensi Usaha Industri Furniture Kota Denpasar - Lilyawati, Lilyawati; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 8, Agustus 2016 (pp. 846-901), 2016)
An effort to accelerate economic development, industrialization is one of the government strategy that aims to improve peoples’s lives. The purpose of this study was to analyze and determine the factors that affect employment and business efficiency in the furniture industry in the city of Denpasar. The sampling technique used is proportional cluster random sampling. Samples in this research were 116 respondents and uses path analysis techniques. Based on that conclusion, capital, and technology positive and significant impact on employment of industrial furniture.Variable capital, technology and labor absorption positive and significant impact on the efficiency of industrial enterprises of furniture in Denpasar. Where as indirect variables which affect the efficiency of business capital and technology affects business efficiency indirectly through employment, so employment is intervening variables that mediate the variable capital and technology to business efficiency.
Keywords: Capital; Technology; Absorption of Labor; Business Efficiency